EU’s strategy and practice of 5G network security - Feng GUO; Yenan JI; Xiaoy HUANG (Dianxin kexue)
5G network is expected to become a key infrastructure for future economic and social development.Nowadays,global competition for 5G has been heating up,with leading operators racing to speed up their 5G deployments.The road-map of engineering and technology for the deployment of 5G networks in EU countries were summarized,the route design,influencing factors as well as time steps for the next phase of 5G networks deployment of them were analyzed.Besides,relevant suggestions for the development of China-EU cooperation in the field of 5G were put forward.